2008
DOI: 10.1039/b809227c
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide and methanol oxidation at platinum catalysts supported on ordered mesoporous carbon: the influence of functionalization of the support

Abstract: The influence of different functionalization treatments of the support on the electrocatalytic activity towards CO and methanol oxidation at platinum nanoparticles deposited on ordered mesoporous carbons (OMC) has been studied for the first time. Before deposition of the metal, the carbon support was functionalized applying several procedures, with the purpose to generate oxygenated groups for anchoring the Pt nanoparticles by the formic acid (FM) and borohydride (BM) reduction methods. Good dispersion of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 61 publications
3
33
0
Order By: Relevance
“…Although oxidative modification may reduce the electron density of Pt on NCNTs, the lower onset potential was measured over Pt on oxidized carbons at similar Pt4f 7/2 (0) BE. This is probably due to the effect of oxygencontaining groups, which promote the oxidation of CO ads [56][57][58]. The preceding catalytic results clearly show the effectiveness of implanting nitrogen functionality on tuning the electronic structure of CNTs-supported Pt catalysts, by which the catalytic properties can be controlled.…”
Section: Catalytic Performance Of Pt/ncntsmentioning
confidence: 77%
“…Although oxidative modification may reduce the electron density of Pt on NCNTs, the lower onset potential was measured over Pt on oxidized carbons at similar Pt4f 7/2 (0) BE. This is probably due to the effect of oxygencontaining groups, which promote the oxidation of CO ads [56][57][58]. The preceding catalytic results clearly show the effectiveness of implanting nitrogen functionality on tuning the electronic structure of CNTs-supported Pt catalysts, by which the catalytic properties can be controlled.…”
Section: Catalytic Performance Of Pt/ncntsmentioning
confidence: 77%
“…A clean surface is recovered in the second cycle coinciding with the voltammogram in the base electrolyte. Common behaviour described in the literature [35] was observed for the three catalysts. From Fig.…”
Section: Characterization Of Pt/pdsn-sno 2 /C Catalystsmentioning
confidence: 54%
“…commercial Pt/C (E-TEK) % 0.5 % 0.15 1 [28] commercial Pt/C (E-TEK) % 0.6 % 0.1 1 [6] hard templating with silica opal, CVD for 2 h at 1000 8C % 0.45 % 0.4 1 [28] hard templating with SBA-15, CVD for 1 h at 900 8C % 0.55 % 0.3 1 [6] hard templating with SBA-15, CVD for 60 min at 500 8C and graphitization at 850 8C % 0.55 % 0.63 1 [16] hard templating with SBA-15, wet impregnation, functionalization in 2 m HNO 3 for 0.5 h % 0.6 0.5 [7,20] ChemPhysChem www.chemphyschem.org supports (pore size: % 3.5 [6] and % 70 nm, [28] respectively) had a higher electrocatalytic activity towards methanol oxidation than standard catalysts. This results from better mass transport of the reactants and products due to higher spatial distribution of platinum particles on the mesoporous material.…”
Section: Methanol Oxidation On Carbon-supported Platinummentioning
confidence: 99%
“…This results from better mass transport of the reactants and products due to higher spatial distribution of platinum particles on the mesoporous material. [7,20] This short summary of OMCs as one example of a porous nanostructured catalyst support for methanol oxidation shows that the characteristics of the carbon support for platinum catalysts have great impact on electrochemical properties in methanol oxidation. Moreover, Calvillo and co-workers reported that functionalization with HNO 3 to create oxygen groups at the surface of OMC improved the performance of methanol oxidation due to better spatial distribution and anchoring of the platinum particles on the support.…”
Section: Methanol Oxidation On Carbon-supported Platinummentioning
confidence: 99%